Evaluation of failure probabilities of mechanical systems under seismic action by the monte-carlo simulation method - Labou, M. (Проблемы прочности, 2008)
Direct Monte-Carlo simulation method (MCS) plays an important role in modern computational methods. For a large class of multidimensional problems of radiative transport theory, the MCS procedure is the only available method allowing the consideration of all varieties of geometric and physical presumptions. This gives rise to computational investigation of actual and practical problems such as neutron- transport problem, reactor shielding, and impurity diffusion in random fields. MCS method enables the determination of the first-passage probability that the system response exceeds prescribed safe domain. In this paper, the failure probabilities of a plate subjected to seismic load are determined using the MCS simulation method. For the purpose of reliability analysis, the von Mises criterion is used to determine the limit state failure. For the seismic load, the statistical model of earthquake- induced ground acceleration proposed by Ruiz and Penzien is used.